Surface Science Tools for Nanomaterials Characterization - Kumar, Challa S.S.R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Fourth volume of a 40volume series on nano science and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Surface Science Tools for Nanomaterials Characterization. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.
Higher Resolution Scanning Probe Methods for Magnetic Imaging -- The Synchrotron Based VUV Resonant Photoemission for Characterisation of Nanomaterials -- SPM for Characterization of PbSe Nanocrystals.-Scanning Probe Microscopy for Nanolithography -- Kelvin Probe Force Microscopy.-Synchrotron Radiation X-ray Photoelectron Spectroscopy -- Scanning Electrochemical Potential Microscopy (SECPM) and Electrochemical STM (EC-STM) -- Band Bending at Metal-Semiconductor and Metal-Ferroelectric Interfaces Investigated by Photoelectron Spectroscopy -- Magnetic Force Microscopy -- High Resolution STM Imaging.-Numerical Simulations on Nanotips for FIM and FEM .-ARPES on Organic Semiconductor Single Crystals Crystalline Films -- FIM-Characterized Tips for SPM -- Scanning Conductive Torsion Mode Microscopy -- Scanning Probe Acceleration Microscopy (SPAM) -- Combining Micromanipulation, Kerr Magnetometry and Magnetic Force Microscopy for Characterization of Magnetic Nanostructures -- Field Ion Microscopy (FIM) -- Non-Contact Atomic Force Microscopy for Characterization of Nanostructures and Beyond.
Keywords: Nanochemistry; Nanotechnology; Nanoscale science; Nanoscience; Nanostructures; Nanochemistry; Nanotechnology; Nanoscale Science and Technology